Principles of antibiotic therapy - Kolář, M (Rozhledy v chirurgii, 2019)
The paper describes the basic sources and principles of antibiotic therapy in contemporary medicine in which the ability to treat bacterial infections may be lost. The main reason for that is the increasing resistance of bacterial pathogens to antibiotics. A possible solution is to implement a comprehensive program of antibiotic stewardship incorporating adequate consideration of indication and selection of antimicrobial agents including appropriate duration and way of administration. Another important component of the comprehensive approach to bacterial resistance and antibiotic therapy is adequately applied antibiotic prophylaxis in surgery.
Keywords: bacteria − antibiotics − resistance − therapy; Anti-Infective Agents; lidé; Anti-Bacterial Agents; antibakteriální látky; antibiotická profylaxe; Antibiotic Prophylaxis; antiinfekční látky; Humans